Valuing Deaf Worlds in Urban India - Friedner, Michele Ilana, 1978- (Book collections on Project MUSE., 2015)
"Although it is commonly believed that deafness and disability limits a person in a variety of ways, Valuing Deaf Worlds in Urban India describes the two as a source of value in postcolonial India. Michele Friedner argues that the experiences of deaf people offer an important portrayal of contemporary self-making and sociality under new regimes of labor and economy in India. Friedner contends that deafness actually becomes a source of value for deaf Indians as they interact with nongovernmental organizations, with employers in the global information technology sector, and with the state. In contrast to previous political economic moments, deaf Indians increasingly depend less on the state for education and employment, and instead turn to novel and sometimes surprising spaces such as NGOs, multinational corporations, multilevel marketing businesses, and churches that attract deaf congregants. They also gravitate towards each other. Their social practices may be invisible to outsiders because neither the state nor their families have recognized Indian Sign Language as legitimate, but deaf Indians collectively learn sign language, which they use among themselves, and they also learn the importance of working within the structures of their communities to maximize their opportunities."--